2018
DOI: 10.1292/jvms.17-0453
|View full text |Cite
|
Sign up to set email alerts
|

A study on periostin involvement in the pathophysiology of canine atopic skin

Abstract: Atopic dermatitis (AD) is a chronic, pruritic, and allergic skin disease in humans and animals, particularly dogs. Canine AD (cAD) has received attention as a spontaneous atopic animal model because domesticated dogs inhabit a human environment, and cAD shares several clinicopathological features with human AD (hAD). In hAD, periostin (PO) is suggested to play a critical role in the enhancement and chronicity of allergic skin inflammation; however, PO involvement in the pathogenesis of cAD is unknown. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…A primary culture of canine dermal fibroblasts was performed as previously described [ 19 ]. Briefly, full-depth skin samples obtained from the chest region of normal dogs were immediately placed in PBS with 1% Antibiotic Antimycotic (Invitrogen Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A primary culture of canine dermal fibroblasts was performed as previously described [ 19 ]. Briefly, full-depth skin samples obtained from the chest region of normal dogs were immediately placed in PBS with 1% Antibiotic Antimycotic (Invitrogen Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that periostin expression was more intense in the skin tissues of AD dogs and correlated with the severity score of chronic histopathological changes (epidermal thickening and fibrosis) and CD3+ cell number in the dermis, similar to that reported in human AD patients [ 20 ]. We also reported that IL-13 possibly derived from T cells stimulates periostin production in both keratinocytes and fibroblasts, and then periostin may play a critical role in the pathophysiology of canine AD, particularly in the enhancement and chronicity of skin lesions [ 19 ]. However, in canine cancer, periostin expression has not been demonstrated, and its role in cancer is not known.…”
mentioning
confidence: 99%
“…In acute lesions, allergic inflammation triggers the release of cytokines such as interleukin (IL-) 4 and IL-13, which induce a T helper 2 (Th2) response [ 1 , 18 , 19 ]. In more chronic skin lesions, CD4+ and CD8+ skin-associated T lymphocytes additionally stimulate the production of various cytokines such as IL-13, IL-22 and IFN-γ [ 20 ].…”
Section: Canine Atopic Dermatitismentioning
confidence: 99%
“…Atopic dermatitis (AD) is a common skin disease in dogs and cats. Its clinical, immunological, histological and pathological features in dogs are so similar to the human counterpart, that canine atopic dermatitis has been suggested as an animal model for human AD [ 1 , 2 ]. In Table 1 some of the similarities and differences are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis is also a common skin disease in dogs and cats. Its clinical, immunological, histological, and pathological features are highly similar between dogs and humans due to which canine atopic dermatitis has been suggested as an animal model for human atopic dermatitis (Mineshige et al 2018). Environmental and lifestyle factors and increasing use of chemicals have often been suggested as contributors to the current situation (Watanabe et al 2018).…”
Section: Discussionmentioning
confidence: 99%